Bowling Young: How Youth Voluntary Associations Influence Adult Political Participation - McFarland, Daniel A.; Thomas, Reuben J. (American Sociological Review, 2006)
Do the voluntary activities of youth increase political engagement in adulthood? Political participation is typically characterized by inertia: reproduced within families, highly correlated with social class, and largely stable after the onset of adulthood. This research illustrates an element of political socialization that occurs just before the transition into full citizenship, that mimics adult civic life, and that can be available regardless of family advantage. The authors use two longitudinal national datasets to identify the kinds of voluntary associations that encourage members to be more politically active later in life. They find that general involvement in extracurricular activities is important, but that in particular, involvement in youth voluntary associations concerning community service, representation, speaking in public forums, and generating a communal identity most encourage future political participation. The authors find these effects net of self-selection and causal factors traditionally characterized in political socialization research. The influence of youth voluntary associations on future political activity is nontrivial and has implications for both democratic education and election outcomes.